2019
DOI: 10.33594/000000057
|View full text |Cite
|
Sign up to set email alerts
|

Specific Features of Fibrotic Lung Fibroblasts Highly Sensitive to Fibrotic Processes Mediated via TGF-β–ERK5 Interaction

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
2
7
1
Order By: Relevance
“…However, CTHRC1 and FHL2 levels in the normal control fibroblast did not change upon TGF-β1 stimulation (CTHRC1: control, P = 0.109 versus lung fibrosis, P = 0.003; FHL2: control, P = 0.360 versus lung fibrosis, P = 0.006; Fig. 3A, B), which suggested that fibrotic fibroblasts specifically responded to TGF-β1 stimulation as previously described [11]. As CTHRC1 is a secreted protein, and a previous report showed that CTHRC1 was present in patient plasma [29], we measured release of CTHRC1 from human lung fibroblasts using enzyme-linked immunosorbent assay (ELISA).…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…However, CTHRC1 and FHL2 levels in the normal control fibroblast did not change upon TGF-β1 stimulation (CTHRC1: control, P = 0.109 versus lung fibrosis, P = 0.003; FHL2: control, P = 0.360 versus lung fibrosis, P = 0.006; Fig. 3A, B), which suggested that fibrotic fibroblasts specifically responded to TGF-β1 stimulation as previously described [11]. As CTHRC1 is a secreted protein, and a previous report showed that CTHRC1 was present in patient plasma [29], we measured release of CTHRC1 from human lung fibroblasts using enzyme-linked immunosorbent assay (ELISA).…”
Section: Resultssupporting
confidence: 77%
“…In addition, rhCTHRC1 stimulated lung fibroblast-mediated gel contraction and migration toward fibronectin, and CTHRC1 knockdown functionally suppressed lung fibroblasts-mediated migration and gel contraction and blocked the TGF-β1 stimulation. Pirfenidone restored TGF-β1- and rhCTHRC1-dependent suppression of BMP4 expression, which was previously reported to reduce proliferation and TGF-β1-induced migration toward fibronectin and synthesis of ECM components, including fibronectin, in lung fibroblast [11, 45, 46]. In the present study, pirfenidone also reduced the levels of the BMP4 antagonist Gremlin1, which was previously implicated in the development of lung fibrosis [47], when stimulated by TGF-β1 and rhCTHRC1.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations